The Dystopia Characteristics in Aldous Huxley Brave New World - Senduk, Jessica S.; Lolowang, Imelda S.; Kumayas, Tirza A. (Journal of English Culture, Language, Literature and Education, 2025)
Dystopian literature is defined as fiction that portrays an uncertain future for society and humanity. This can be considered a warning to society members to be aware of their surroundings and the potential for horrible things to happen without their knowledge. One example of literary works that portraying dystopian characteristics is Brave New World (1932) by Aldous Huxley. Thus, this research aims to identify and reveal the dystopia characteristics in the novel Aldous Huxley’s Brave New World using dystopian characteristics theory by Terri Chung. This research uses qualitative research because the data is in the form of word. In analyse the data, the researcher are using objective approach which focuses on the novel’s intrinsic elements, including its characters, setting, and themes. The result of this research shows that the novel contains all nine dystopia characteristics from Chung’s theory including propaganda, restricted knowledge, social control, dehumanization, and the illusion of a perfect society. The character, John the Savage, represents the struggle of true human experience in a world dominated by artificial happiness and control. His tragic fate highlight the novel warning that society prioritizing stability over freedom ultimately dehumanizes its citizens. The results showed that Brave New World novel portrays a dystopia society that appears perfect on the surface but is actually controlled and oppressive